Q. 515.0( 1 Vote )

# If y = A e ^{– kt} cos (pt + c), prove that , where n^{2} = p^{2} + k^{2}.

Answer :

Formula: –

Given: –

Differentiating w.r.t t

Differentiating w.r.t t

Hence proved

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

How to find Maxima & Minima?43 mins

Special Quiz on Photosynthesis in Higher Plants - Test Yourself64 mins

Interactive quizz on tangent and normal, maxima and minima43 mins

Interactive quiz on maxima and minima48 mins

Tangent & Normal To A Curve53 mins

Test your knowledge of Tangents & Normals (Quiz)52 mins

Tangents & Normals (Concept Builder Class)55 mins

Determinants of Matrices of different order59 mins

Different high order thinking questions based on DNA structure39 mins

Acidic & Basic order in Organic Chemistry44 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

If y = tan^{-1}x, find in terms of y alone.

If y = sin^{-1} x, show that

If y = 3 cos(log x) + 4 sin(log x), show that

Mathematics - Board Papers

If x = t^{2}, y = t^{3}, then is

If x = a cos θ + b sin θ, y = a sin θ – b cos θ, show that

Mathematics - Board PapersIf prove that

Mathematics - Exemplar

If y =(tan^{–1}x)^{2}, show that

If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}